The Effect of the Edmodo-Assisted Discovery Learning Model on Students’ Scientific Literacy Ability - Yolida, Berti; T. Marpaung, Rini Rita; Priadi, median Agus; Sulika, Aripati (Biosfer: Jurnal Tadris Biologi, 2022)
This study aims to see how the Edmodo-assisted Discovery Learning model affects students' scientific literacy skills. This study is a quasi-experimental design with a pretest-posttest non-equivalent control group. The experimental class is taught using the Edmodo-assisted discovery learning methodology. Data were collected using a pretest and a posttest to measure the increase in students' scientific literacy skills. The experimental class received an N-Gain of 0.51, while the control class received an N-Gain of 0.29. The significance of the Independent Sample t-test on student N-Gain scores is 0.000, which is lower than 0.005, indicating that the Edmodo-assisted discovery learning model has a substantial effect on students' scientific literacy skills. The results of the questionnaire analysis also revealed that students were enthusiastic about Edmodo-assisted discovery learning. As a result, the Edmodo-assisted discovery learning model considerably impacts students' scientific literacy skills.ABSTRAK: Penelitian ini bertujuan untuk mengetahui pengaruh model Discovery Learning berbantu Edmodo terhadap kemampuan literasi sains peserta didik. Penelitian ini merupakan kuasi eksperimen dengan desain pretest-posttest non equivalent control group design. Model discovery learning berbantu Edmodo diterapkan pada kelas eksperimen. Pengumpulan data dilakukan dengan menggunakan pretest dan posttest untuk mengetahui peningkatan kemampuan literasi sains peserta didik. Hasil penelitian menunjukan kelas eksperimen mendapatkan N-Gain sebesar 0,51 sedangkan kelas kontrol mendapatkan N-Gain sebesar 0,29. Uji Independen Sample t-test terhadap skor N-Gain siswa menunjukkan signifikansi 0.000 < 0,005 yang berarti model discovery learning berbantu Edmodo berpengaruh signifikan terhadap kemampuan literasi sains peserta didik. Hasil analisis angket juga menunjukan respon yang baik dari siswa terhadap pembelajaran discovery learning berbantu edmodo. Dengan demikan dapat disimpulkan bahwa model discovery learning berbantu Edmodo berpengaruh signifikan terhadap kemampuan literasi sains peserta didik.